Online PdP new normal for UMP students - UMP, PNC (2020)
Pekan, 1 June 2020 - Students at Universiti Malaysia Pahang (UMP) started their virtual classes in line with the new normal in Online Teaching and Learning (PdP-DT) implemented this 1 June.